The vulture fund - Frey, Stephen W. (New York : Dutton, 1996)
A CIA director with presidential ambitions, but not the cash, hires Arabs to launch a campaign of terror to precipitate economic chaos in the U.S. This will enable him to buy property at a cheap price, later selling it at a profit. The main protagonist is the banker raising money for the purchases.
National College of Business and Arts
Keywords: Investment banking -- Corrupt practices -- Fiction; Detective and mystery fiction